Mark Haddon’s The Curious Incident of the Dog in the Night-Time, Narrative Fallibility, and the Young Adult Reader - Jessica Allen Hanssen (Literature, 2024)
The Curious Incident of the Dog in the Night-Time by Mark Haddon presents a remarkably complex narrator, 15-year-old Christopher Boone. Due to his implied autism spectrum condition, Christopher is possibly the ultimate in “reliable” narrators: he struggles to articulate emotions and is incapable of telling or understanding lies. His point of view (POV) is an extreme form of first-person limited, with Christopher at times seeming (or even yearning) to be more computer than human. The limitations of Christopher’s experience are reflected in his narrative self-presentation, and while, ordinarily, these would damage any sort of achieved authority, they instead underscore the book’s powerful thematic messages. Christopher’s narrative fallibility echoes the developmental stage of its crossover young adult (YA) audience: Curious Incident works with fallibility to establish a strong narrative voice that inspires an empathetic connection between Christopher and his implied reader. This article therefore considers how narrative fallibility is linked to constructions of adolescence in The Curious Incident of the Dog in the Night-Time, and further explores the relationship between the narrator and the implied reader(s). Positioned within narratology-based theories and secondary research on Haddon and representations of neurodiversity in YA literature, it provides guidance for teachers and scholars who might question the value of authenticity in this or similar novels.